Regional wage differences and segmentation in Brazil's urban labor markets - William D. Savedoff (Institute for Applied Economic Research (ipea), 2015)
This paper investigates whether the workforce in Brazil is geographically segmented by analyzing variation in workers' earnings. It finds that standard market explanatlons for regional wage disparities, such as variations in the cost of living or workforce quality, can explaln only a part of the disparities. The paper concludes that geographical obstacles to factor flows are not slgnificant in Brazil. Rather, the persistence of regional wage differentials, in spite of the increasing integration of the Brazilian economy, can be largely attributed to regional variation in the composition of labor demand.
Keywords: 330